Clinical-epidemiological study of patients with cancer in the mouth floor - René Morales Basulto; Yoel Michel Reina Rodríguez; Jordanis Viamontes Beltrán (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Background: the floor of the mouth constituted only by soft tissues and lacking of plans of osseous reference represents one of the most delicate areas of the oral cavity. The appearance of malignat neoplasias is frequently seen in this anatomic site which is the cause of medical consultations, surgeries, oncologic treatments and deaths. Objective: to characterize the population of patients with cancer on the floor of the mouth based on the sociodemographic variables such as age, sex, riskfactors, clinical symptoms of the disease and anatomic-pathological characteristics of the lesion. Methods: A descriptive and observational retrospective study during 7 years was carried out in the object of study population, which attended the Maxillofacial Surgery Consultation at Maria Curie Oncologic Hospital from January 2011 to January 2018. The study included 34 patients diagnosed with cancer on the floor of the mouth based on the interview, the physical examination and the biopsy. Results: There was a great incidence in the age groups between 60 and 69 years old (41,17 %), belonging to the male sex (76,47%).The most common risk factors were nicotine (73,52 %) and alcoholism (38,23 %). Among the clinical manifestations, the pain was the most common clinical symptom and there was a prevalence of ulcerative lesions (35.29%). Conclusions: There was a prevalence in the age groups older than 60 years old and male sex,the population showed a marked nicotine and alcohol addiction. The pain was the main symptom in the first consultation and there was a prevalence of ulcerative lesions.